2014
DOI: 10.1111/cns.12272
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Inhibition Interrupts the Progression of Seizures in Immature Rats and Reduces Hippocampal Damage

Abstract: These results suggest P2X7 receptor antagonists may be suitable as frontline or adjunctive treatments of pediatric status epilepticus or other early-life seizures, particularly when associated with brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 52 publications
6
32
1
Order By: Relevance
“…Early attention was on the role of P1 adenosine receptors in epileptic seizures, but more recently P2X4 and P2X7 receptor antagonists have been explored as neuroleptic agents [8,83,84]. P2Y12 knockout mice exhibited reduced seizure-induced increases in microglial process numbers and worsened kainate-induced seizure behaviours [85].…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…Early attention was on the role of P1 adenosine receptors in epileptic seizures, but more recently P2X4 and P2X7 receptor antagonists have been explored as neuroleptic agents [8,83,84]. P2Y12 knockout mice exhibited reduced seizure-induced increases in microglial process numbers and worsened kainate-induced seizure behaviours [85].…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…Prolonged exposure to ATP leads to formation of a large opening (termed a macropore) in vitro, although the physiologic significance of this macropore formation is not clearly understood. One of the hallmark features of P2X7 activation is release of the proinflammatory cytokine interleukin (IL)-1b (Solle et al, 2001), which in turn may contribute to neuroinflammation and pain (Chessell et al, 2005;North and Jarvis, 2013), mood disorders (Iwata et al, 2013;Chrovian et al, 2014), and neurodegenerative disorders, such as Alzheimer's disease , multiple sclerosis (Sharp et al, 2008), and epilepsy (Engel et al, 2012;Mesuret et al, 2014). In addition to IL-1b, P2X7-dependent release of glutamate (Andó and Sperlágh, 2013;Ficker et al, 2014), cathepsins (Clark et al, 2010), and chemokines (Shiratori et al, 2010) have been reported, and all of these mediators can serve as "gliotransmitters" aiding in the neuroimmune cross-talk and modulating synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research to discover new antagonists of P2X7R has been growing and has gained high financial support from the pharmaceutical industry (Gunosewoyo & Kassiou, ). P2X7R is implicated in many pathological processes, including neuropathic pain, inflammatory, and neurodegenerative diseases and cancer (Broom et al, ; Corrêa, Marques da Silva, Abreu Moreira‐Souza, Vommaro, & Coutinho‐Silva, ; Diaz‐Hernandez et al, ; Lee et al, ; Li et al, ; Lister et al, ; Mesuret et al, ; Raffaghello et al, ; Teixeira et al, ; Zhao et al, ). The development of new antagonists with efficacy and safety that could be applied in clinical treatments is one of the major challenges of purinergic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…P2X7R has roles in many physiological processes, such as activation of immune and inflammatory responses and cell death (Coddou, Yan, Obsil, Huidobro‐Toro, & Stojilkovic, ). Moreover, it was suggested that P2X7R participates in several pathologies, including neurodegenerative, inflammatory and infectious diseases, neuropathic pain, rheumatoid arthritis, and cancer (Broom et al, ; Corrêa, Marques da Silva, de Abreu Moreira‐Souza, Vommaro, & Coutinho‐Silva, ; Diaz‐Hernandez et al, ; Lee et al, ; Li, Liang, & Chen, ; Lister et al, ; Mesuret et al, ; Raffaghello, Chiozzi, Falzoni, Di Virgilio, & Pistoia, ; Teixeira, de Oliveira‐Fusaro, Parada, & Tambeli, ; Zhao et al, ). Despite its relevance as a therapeutic target, P2X7R antagonists are still not applied in clinical treatment.…”
Section: Introductionmentioning
confidence: 99%